How dependent is climate change projection of Indian summer monsoon rainfall and extreme events on model resolution? - Rajendran K; Jayasankar CB; Kitoh A; Sajani S (Current Science, 2013)
Advances in climate modelling now provide the opportunity for utilizing global general circulation models (GCMs) at very high resolution for projections of future climate and extreme events. Diagnostics of global atmospheric GCM simulations at different horizotal resolutions of 20,60,120 and 180 km reveals the marked skill of 20 km mesh GCM (MRI-AGCM3.2S) in capturing regional characteristics of climatological summer monsoon railfall over India and its frequency distribution, and mean annual variation of rainfall over most of the homogeneous regions of India. Future projections by time-slice simulations of MRI-AGCM3.2S under global warming scenario show widespread but spatially varying increase in rainfall over interior regions of peninsular, west central, central northeast and North East India (~5-20;of seasonal mean) and significant reduction in orographic rainfall over the west coast (~10-15;, consistent with the recent observed trends). MRI-AGCM3.2S projects spatially heterogeneous increase in warm days and extreme hot events (highest decile) over India. Projected changes in extreme rainfall events (above 95 percentile) show intensification of extreme rainfall over most parts of India by the end of the century with opposite change over the west coast. Ultra-high-resolution is found to be crucial not only for realistic mean summer monsoon simulation, but for achieving useful future projections of Indian monsoon and extremes. At lower resolution, the simulations fail to capture the observed characteristics of present-day monsoon rainfall and its spatial heterogeneity, and projections lackuseful regional climate information. Thus, consideration of fine scale processes are critical for reasonable probabilistic projection of regional scale climate change.
Keywords: Climate change projection; Extreme events; General circulation model; Ultra-high resolution